Hemodynamics in neonates with polycythemia before and after partial exchange transfusion: an observational study - Kallimath, Aditya; Kolkur, Karthik; Malshe, Nandini; Klimek, Jan; Suryawanshi, Pradeep (Frontiers in Pediatrics, 2024)
The current recommendations for the management of neonatal polycythemia are that partial exchange transfusion (PET) should be performed if the hematocrit is > 70% in an asymptomatic neonate, or if the haematocrit is > 65% in a symptomatic neonate. The hemodynamic effects of PET for neonatal polycythemia have not been well researched.Objectives: To evaluate the hemodynamic effects of PET in neonates with polycythemia.Methodology: Prospective observational study conducted in a neonatal intensive care unit of a tertiary care teaching hospital enrolling 21 neonates with polycythemia who underwent PET. Hemodynamic and echocardiographic parameters were obtained prior to PET and 6 hours after procedure.The mean gestational age of neonates with polycythemia was 35.08 + 2.35 weeks with a mean birth weight of 1929 + 819.2 grams. There was a significant improvement noted in heart rate and oxygen saturation post PET procedure (p < 0.05). Right ventricular systolic function parameters showed significant improvement (Tricuspid annular plane systolic excursion, fractional area change, right ventricular output) (p < 0.05). Left ventricular function parameters showed significant improvement (Fractional shortening, left ventricular output, E:A ratio) (p < 0.05). Resolution of symptoms was noted after PET procedure with no adverse events associated with PET.PET maybe effective in improving heart rate and oxygen saturation levels in polycythemic neonates. It has good short-term hemodynamic stability with improvement in right ventricular systolic, as well as left ventricular systolic and diastolic function. It is a safe and effective procedure with minimal adverse effects. Further studies with larger sample size and a control group would be required to corroborate our findings.